Sphingosine kinase 1 is required for TGF-β mediated fibroblast-to-myofibroblast differentiation in ovarian cancer - Jessica A. Beach; Paul‐Joseph Aspuria; Dong‐Joo Cheon; Kate Lawrenson; Hasmik Agadjanian; Christine Walsh; Beth Y. Karlan; Sandra Oršulić (2015)
// Jessica A. Beach 1, 2, * , Paul-Joseph P. Aspuria 1, * , Dong-Joo Cheon 1 , Kate Lawrenson 1 , Hasmik Agadjanian 1 , Christine S. Walsh 1, 3 , Beth Y. Karlan 1, 3 , and Sandra Orsulic 1, 3 1 Women's Cancer Program at the Samuel Oschin Comprehensive Cancer Institute, Los Angeles, CA, USA 2 Graduate Program in Biomedical Science and Translational Medicine, Cedars-Sinai Medical Center, Los Angeles, CA, USA 3 Department of Obstetrics and Gynecology, David Geffen School of Medicine, University of California, Los Angeles, CA, USA * These authors have contributed equally to this work Correspondence to: Sandra Orsulic, e-mail: Sandra.Orsulic@cshs.org Keywords: sphingosine kinase 1 (SPHK1), cancer-associated fibroblast (CAF), transforming growth factor-beta 1 (TGF-β1), sphingosine-1-phosphate (S1P), microenvironment Received: August 18, 2015 Accepted: December 05, 2015 Published: December 21, 2015 ABSTRACT Sphingosine kinase 1 (SPHK1), the enzyme that produces sphingosine 1 phosphate (S1P), is known to be highly expressed in many cancers. However, the role of SPHK1 in cells of the tumor stroma remains unclear. Here, we show that SPHK1 is highly expressed in the tumor stroma of high-grade serous ovarian cancer (HGSC), and is required for the differentiation and tumor promoting function of cancer-associated fibroblasts (CAFs). Knockout or pharmacological inhibition of SPHK1 in ovarian fibroblasts attenuated TGF-β-induced expression of CAF markers, and reduced their ability to promote ovarian cancer cell migration and invasion in a coculture system. Mechanistically, we determined that SPHK1 mediates TGF-β signaling via the transactivation of S1P receptors (S1PR2 and S1PR3), leading to p38 MAPK phosphorylation. The importance of stromal SPHK1 in tumorigenesis was confirmed in vivo , by demonstrating a significant reduction of tumor growth and metastasis in SPHK1 knockout mice. Collectively, these findings demonstrate the potential of SPHK1 inhibition as a novel stroma-targeted therapy in HGSC.